Comparison of surgical conditions following premedication with oral clonidine versus oral diazepam for endoscopic sinus surgery: A randomized, double-blinded study - Rohini V Bhat Pai; Santhoshi Badiger; Roopa Sachidananda; Santhosh Mysore Chandramouli Basappaji; Raghunath Shanbhag; Raghavendra Rao (Wolters Kluwer Medknow Publications, 2016)
Background and Aims: Endoscopic sinus surgery (ESS) provides a challenge and an opportunity to the anesthesiologists to prove their mettle and give the surgeons a surgical field which can make their delicate surgery safer,more precise and faster. The aim of the study was to evaluate the surgical field and the rate of blood loss in patients premedicated with oral clonidine versus oral diazepam for endoscopic sinus surgery. Material and Methods: ASA I or II patients who were scheduled to undergo ESS were randomly allocated to group D (n = 30) or group C (n = 30). The patients' vital parameters, propofol infusion rate, and rate of blood loss were observed and calculated. The surgeon, who was blinded, rated the visibility of the surgical field from grade 0-5. Results: In the clonidine group, the rate of blood loss, the surgical time, propofol infusion rate was found to be statistically lower as compared to the diazepam group. Also a higher number of patients in the clonidine group had a better surgical score (better surgical field) than the diazepam group and vice versa. Conclusions: Premedication with clonidine as compared to diazepam, provides a better surgical field with less blood loss in patients undergoing ESS.